Dormancy breaking and advancement of maturity induced by hydrogen cyanamide: a strategy to improve profits in sweet cherry production - Raffo Benegas, Maria Dolores; Mañueco, María Lucía; Candan, Ana Paula; Santagni, Adalberto; Menni, María Fernanda (ISHS, 2025)
Trabajo presentado al VI International Cherry Symposium, Reñaca (Chile), 2009